SPONTANEOUS RUPTURE OF ARTERIOVENOUS MALFORMATION: ICU BASED BRAIN RESUSCITATION - Panji, Putu Agus Surya; Aryabiantara, I Wayan; Suranadi, I Wayan; Parami, Pontisomaya; Wibisana Kurniajaya, I Gusti Agung Made (Bali Journal of Anesthesiology, 2017)
Arteriovenous malformations (AVM) is a relatively rare intracranial abnormality. Generally, it caused by congenital abnormalities that recognized after the bleeding started. Spontaneous intracranial bleeding after AVM rupture is an emergency condition and require immediate treatment to reduce mortality rate. After stabilization of intracranial bleeding due to AVM rupture, secondary injury may occur hours or even days after the inciting traumatic event. The injury may result from impairment or local declines in cerebral blood flow (CBF) after brain injury. The decrease in CBF is the result of local edema, hemorrhage, or increased intracranial pressure (ICP). An adequate brain resuscitation is needed to decrease brain edema and intracranial pressure by achieving several targets and avoid things that can interfere with CBF. A recovery phase should be given to the patient with rupture of AVM before going to definitive therapy.